Bearing witness to crime and social justice - Quinney, Richard (SUNY series in deviance and social control., 2001)
"Featuring both scholarly and autobiographical writings, Bearing Witness to Crime and Social Justice follows Richard Quinney's development as a criminologist. Quinney's criminology is a critical criminology which he describes as a journey of witnessing to crime and social justice. Quinney's travels from the 1960s through the 1990s show a progression of ways of thinking and acting: from the social constructionist perspective to phenomenology, from phenomenology to Marxist and critical philosophy, from Marxist and critical philosophy to liberation theology, from liberation theology to Buddhism and existentialism. Along this journey, Quinney adopts a more ethnographic and personal mode of thinking and being. Each new stage of development incorporates what has preceded it; each change has been motivated by the need to understand crime and social justice in another or more complex way, in a way excluded from a former understanding. Each stage has also incorporated changes that were taking place in Quinney's personal life. Ultimately, there is no separation between life and theory, between witnessing and writing."--Jacket